Salivary cell-free DNA methylation analysis for oncological monitoring of surgical resection of oral squamous cell carcinoma - Saidak, Zuzana; Milly, Marie; Louandre, Christophe; Colin, Emilien; Rusu, Pia-Manuela; Paasche, Agnes; Dakpe, Stephanie; Testelin, Sylvie; Galmiche, Antoine (Frontiers in Oral Health, 2025)
ObjectiveNon-invasive analysis of tumor DNA in biological fluids offers promising perspectives for the oncological monitoring of cancer patients. Cancer-specific DNA methylation marks are detectable in the saliva of Oral Squamous Cell Carcinoma (OSCC) patients. We set up a salivary liquid biopsy approach for the oncological monitoring of OSCC referred for surgical resection.Material and methodsWe analysed DNA methylation in TCGA-OSCC to identify genes with high methylation levels in tumor vs. matched non-tumor tissue. Cell-free DNA (cfDNA) methylation levels of selected genes were analysed in the saliva of OSCC patients (n = 30) before/after complete surgical resection by High Resolution Melting (HRM) analysis, and compared to non-cancer controls.ResultsWe identified five genes with higher DNA methylation levels in OSCC compared to matching non-tumor tissue that were analysable by HRM, and were independent of tumor stage, etiology or age. In 70% of OSCC, at least one of the five cfDNA methylation marks was detectable before surgery. Complete surgical resection led to a significant disappearance of salivary cfDNA methylation marks. In 52% of patients, we noted the persistence of at least one mark, shown to be related to close/positive surgical margin status. In one patient resected with R0 margin, the persistence of ASCL1 methylation preceded tumor recurrence by 4 months.ConclusionSalivary cfDNA methylation analysis offers a minimally invasive method to monitor the effectiveness of surgical resection of OSCC. Future studies with a larger cohort and longer follow-up are required to validate its use in this context.